Overexpression of the GmPM35 Gene Significantly Enhances Drought Tolerance in Transgenic Arabidopsis and Soybean - Xinyu Wang; Yao Sun; Rui Wang; Xinyang Li; Yongyi Li; Tianyu Wang; Zhaohao Guo; Yan Li; Wenxi Qiu; Shuyan Guan; Qi Zhang; Piwu Wang; et al. (Agronomy)
Drought stress is one of the major adversity stresses affecting soybean (Glycine max [L.] Merr.) yield. Late embryogenesis abundant protein (LEA protein) is a large family of proteins widely distributed in various types of organisms, and this class of proteins plays an important role in protecting proteins, membrane lipids, and lipids inside the cell. The soybean GmPM35 gene is a member of the LEA_6 subfamily. The expression of the GmPM35 gene was significantly increased after drought stress in soybeans. A subcellular localization assay confirmed that the gene acts on the cell membrane. Against wild-type Arabidopsis thaliana, we found that Arabidopsis lines overexpressing the GmPM35 gene were significantly more drought-tolerant at germination and seedling stages under drought stress. To further investigate the drought tolerance function of this gene in soybeans, nine overexpression lines of the T3 generation soybean GmPM35 gene and two editing lines of the T3 generation soybean GmPM35 gene were obtained by Agrobacterium-mediated method using a wild-type soybean strain (JN28) as a receptor. Germination rate, root length, chlorophyll (CHL) content, Proline (Pro) content, malondialdehyde (MDA) content, superoxide anion (O2•−) content, hydrogen peroxide (H2O2) content, (NBT, DAB) staining, and activities of antioxidant enzymes (CAT, SOD, POD), and photosynthetic physiological indexes of the three different types of strains were measured and analyzed before and after drought stress. Combined with the results of rehydration experiments and physiological and biochemical indices, we found that overexpression of the GmPM35 gene protected the activities of antioxidant enzymes under drought stress. The activities of superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) were increased by an average of 34.28%, 26.12%, and 30.01%, respectively, in soybean plants overexpressing the GmPM35 gene compared with wild-type soybeans. Under drought stress conditions, soybean plants overexpressing the GmPM35 gene showed an average increase of 76.81% in photosynthesis rate (Pn), 39.8% in transpiration rate (Tr), 126% in stomatal conductance (Gs), 47.71% in intercellular CO2 concentration (Ci), and 26.44% in instantaneous water use efficiency (WUEi). The improvement of these indexes helped to reduce the accumulation of reactive oxygen species (ROS) in the plants. In addition, we found that under drought stress, the MDA content was reduced by an average of 18.8%, and the Pro content was increased by an average of 60.14% in soybean plants overexpressing the GmPM35 gene, and the changes in these indexes indicated that the plants had stronger antioxidant and osmoregulatory capacities in response to drought stress. In summary, this experiment demonstrated that the GmPM35 gene plays an important role in soybean tolerance to drought stress, and by overexpressing the GmPM35 gene, soybean plants can better tolerate drought stress and maintain normal physiological functions.